Combining Parent and Child Training for Young Children with ADHD - Webster-Stratton, Carolyn (2011)
The efficacy of the Incredible Years parent and child training programs is established in children diagnosed with oppositional defiant disorder (ODD) but not among young children whose primary diagnosis is attention-deficit/hyperactivity disorder (ADHD). We conducted a randomized control trial evaluating the combined parent and child program interventions among 99 children diagnosed with ADHD (ages 4–6). Mother reported significant treatment effects for appropriate and harsh discipline, use of physical punishment, and monitoring, whereas fathers reported no significant parenting changes. Independent observations revealed treatment effects for mothers' praise and coaching, mothers' critical statements, and child total deviant behaviors. Both mothers and fathers reported treatment effects for children's externalizing, hyperactivity, inattentive and oppositional behaviors, and emotion regulation and social competence. There were also significant treatment effects for children's emotion vocabulary and problem-solving ability. At school teachers reported treatment effects for externalizing behaviors and peer observations indicated improvements in treated children's social competence.